Zur politischen Ökonomie von Defiziten und Kapitalsteuerwettbewerb - Athanassios Pitsoulis; Jens Peter Siebel (OrdnungsPolitisches Portal (OPO), 2009)
We connect the theories of strategic debt and tax competition in a model and explore whether capital mobility coupled with a strategic debt effectively tames Leviathan. Our proposition is that in the case of a small open economy international tax competi-tion for mobile capital opens the way to a previously unexplored sort of strategic deficit. The incumbent conservative government builds a reelection strategy on the downwards pressure on mobile factor tax rates caused by tax competition the liberal successor will be exposed to. As a result it can raise its chances to be reelected by tying the successor's hands on expenditure issues.
Keywords: 330; Structure and Scope of Government; State and Local Budget and Expenditures; Interjurisdictional Differentials and Their Effects